2015
DOI: 10.3357/amhp.4068.2015
|View full text |Cite
|
Sign up to set email alerts
|

Dodecafluoropentane (DDFPe) and Decompression Sickness-Related Mortality in Rats

Abstract: We conclude that DDFPe is not an effective nonrecompressive treatment for DCS in rodents. Sheppard RL, Regis DP, Mahon RT. Dodecafluoropentane (DDFPe) and decompression sickness-related mortality in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Administration of a F-pentane P-SNEs (Echogen) increased central venous O 2 tension and effectively enhanced tissue denitrogenation under O 2 breathing in pigs [391]. Another study with a F-pentane P-SNE found no effectiveness in rodents [392]. An undesirable increase of pulmonary artery pressure and no effect on survival were observed with Oxycyte, also in swine [393].…”
Section: Delivery or Removal Of Therapeutic Gases Other Than Oxygenmentioning
confidence: 99%
“…Administration of a F-pentane P-SNEs (Echogen) increased central venous O 2 tension and effectively enhanced tissue denitrogenation under O 2 breathing in pigs [391]. Another study with a F-pentane P-SNE found no effectiveness in rodents [392]. An undesirable increase of pulmonary artery pressure and no effect on survival were observed with Oxycyte, also in swine [393].…”
Section: Delivery or Removal Of Therapeutic Gases Other Than Oxygenmentioning
confidence: 99%
“…But not every PFC preparation appears to be useful. In a recent study by Sheppard et al dodecafluoropentane (DDFPe) was associated with a high mortality and showed no beneficial effects in a rat model with DCS (Sheppard et al 2015). Randsoe et al demonstrated that under normobaric conditions, the combination of oxygen breathing and PFC leads to accelerated reduction of bubbles and that both therapies complement each other (Randsoe and Hyldegaard 2009).…”
Section: Main Textmentioning
confidence: 99%
“…Several studies in different animal species showed an increase in pulmonary arterial pressure (PAP) (Hall et al 1985; Spiess et al 2009; Smith et al 2012). This observation, for example in sheep, is even more relevant, because severe DCI itself can cause high PAP due to nitrogen-bubble-associated mechanical obstruction or indirectly by endothelial effects with vasoconstriction (Josephson 1970; Sheppard et al 2015). A recent mixed-sex swine study using the emulsified perfluorocarbon Oxycyte™ revealed a prolonged PAP increase in this species (Mahon et al 2015).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation